Active Control of Electromagnetically Induced Transparency Analog in Terahertz MEMS Metamaterial. Issue 4 (12th January 2016) - Pitchappa, Prakash; Manjappa, Manukumara; Ho, Chong Pei; Singh, Ranjan; Singh, Navab; Lee, Chengkuo
Abstract : Independent control of near‐field‐coupled bright and dark resonators for active modulation and frequency tuning of electromagnetically induced transparency analogs in the terahertz spectral region is experimentally demonstrated. An out‐of‐plane reconfigurable microcantilever is the active element for resonator control. The proposed microelectromechanical systems (MEMS) metamaterial is miniaturized, electrically controlled, and can achieve up to an order of magnitude change in THz group‐delay bandwidth product.